(untitled) (Research, Society and Development, 2020)
The scientific and technological development of society requires techniques for measuring physical quantities that are increasingly more precise, thus making experimental processes in Physics quite important. In this sense, the determination of international measurement standards makes the results of a particular experiment, easily reproducible. However, due to the impossibility of carrying out certain experiments, it is necessary to obtain estimates of the quantities involved, in order to know whether more precise calculations or more sophisticated apparatus will be necessary. In the course of Electromagnetism – materials and equipment, for example, we can mention the electrical resistivity of metals, an important quantity in several branches of optics. Therefore, in this work, we propose a simple and low cost experimental method to estimate the ratio of the electrical resistivities of two metals (copper to aluminum) using neodymium magnets and a stopwatch. This experimental activity can be easily performed in any Physics laboratory at both the High School level and the undergraduate level in the exact science courses.